Agathidium mexicanum Hendrichs, 1979: Types rediscovered - Navarrete-Heredia, José L.; Sandoval, Liliana P.; Zaragoza-Caballero, Santiago (Zootaxa, 2020)
Agathidium mexicanum Hendrichs, 1979: 106 is the single Mexican species of Leiodidae described by a Mexican entomologist: Chemical Engineer Jorge Hendrichs. As an amateur coleopterist he made a beetle collection of 18,400 specimens, adequately labeled by his wife and daughter. Most of the specimens are now in the entomological collection of the Instituto de Biología, UNAM. He published 12 papers, one of them devoted to the description of one leiodid species: Agathidium mexicanum Hendrichs, 1979. Type specimens of A. mexicanum were collected in Estado de Mexico and Distrito Federal (now Ciudad de México) localities (type locality: Cerro Tlaloc, Estado de México). The type series as described in the original description was constituted by 13 specimens: Holotype (male), allotype (female) and, 11 paratypes (6 males and 5 females). For specific details, data of the material examined is fully included (Hendrichs 1979: 110):